Spontaneous Skin Lesion in a Canine Patient without Defined Breed (Homoeopathy for All, 2024)
The cutaneous clinical manifestation  characterized by deep dermatitis  with granulomatous reaction,  appearance of an edematous,  circular and alopecic nodule was  found abruptly in a 6-year-old  female canine patient. Diagnosed  with Lupus Erythematosus due to  the presence of major symptoms,  the causes of kerion were excluded  by the species Microsporum canis,  M. gypseum and Trichophyton  mentagrophytes, which were found  to be absent in the cytology, fungal  and bacterial cultures of the present  case. Using Causticum 30 cH, three  globules, twice a day, the patient's  inflammatory process ceased on  the third day, turning the lesion  into a wound that healed on the  fifteenth day. Complete rehairing  of the affected area was observed  on the thirtieth day. Immunological  parameters that affected skin  morphometry in the initial phase,  showed positive results after the  use of homeopathy, reflecting the  magnitude of the therapy adopted in  dermatopathies.
Keywords: alopecia; autoimmune; Causticum